Pengaruh Penggunaan Wordwall Terhadap Hasil Belajar Mahasiswa MKU Bahasa Jepang UNP - Rita Arni; Prisyanti Suciaty (Vocational College of Diponegoro University, 2023)
Educational game media with wordwall has many unique templates that can be used for learning Japanese language. Therefore, researcher want to test how the effect of educational games with wordwall is on the learning outcomes of MKU Japanese language students at UNP, semester January-June 2023. This study aims to determine the effect of using educational games with wordwall on student learning outcomes of MKU Japanese language students at UNP. The research design used is a quasi experiment. This research is a quantitative research with an experimental design with a posttest only control group design. The population of this study were all MKU Japanese language students at UNP, in the January-June 2023 semester. The data was collected from a research sample of 80 people consisting of two classes. From the results of the independent sample test t-test, it was concluded that H1 was accepted at the sig level of sig 0.0001 <0.05, which means that student learning outcomes in the experimental class were superior to those in the control class. In other words, the use of wordwall educational games has an effect on the learning outcomes of MKU Japanese language students at UNP.